FORMATION OF COMMUNICATION CULTURE OF SCHOOLCHILDREN IN THE PROCESS OF GROUP WORK AT THE LESSONS OF PRIMARY SCHOOL - Lapshyna, Iryna; Lyubchak, Lyudmila; Franchuk, Nataliia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The authors of the article comment on the difficulties of the formation of communication culture among primary school pupils from the first days of training; explain the need for such educational work by the systematic use of new educational technologies at the lessons and in extracurricular activities of primary school pupils. It is represented the psychological and pedagogical prerequisites for the formation of communication culture from the point of view of cultural and communicative approaches to the organization of the educational environment. By means of the survey of primary school pupils and their teachers, the problematic moments of the organization of group work at the lessons are revealed. The researchers present the system of educational, cognitive and communicative situations for the formation of communication culture skills in the process of group work of pupils and comment on its productivity.